The Effect of 5-E Inquiry-Based IPAS Learning on Critical Thinking Skills and Process Skills of Students of SDN 3 Kalibombong - Widian Mustakim; Subuh Anggoro (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to determine the effect of IPAS learning to improve students' critical thinking ability and process skills. The type of research used is descriptive quantitative. This research uses a 5-E based inquiry learning model. The 5-E inquiry approach is a learning approach that is oriented towards student activeness. The discussion in this study discusses the implementation of critical thinking and process skills in the realm of Natural Science subjects. The sample of this study were fourth grade students of SDN 3 Kalibombong, totaling 22 students. The data collection techniques used were tests, questionnaires, field notes and documentation. The research data were processed using a simple linear regression test with the results for the effect of 5-E Inquiry-based IPAS learning on critical thinking skills tcount of 4.044> ttable 2.086, meaning tcount> ttable.For the effect of 5-E Inquiry-based IPAS learning on process skills 5.184> ttable 2.086, meaning tcount> ttable. Based on the results of this study, it shows that there is an effect of 5-E Inquiry-based IPAS learning on critical thinking skills and process skills of fourth grade students of SDN 3 Kalibombong in the 2024/2025 academic year.